Cambridgeshire introductions - Thorn, Frank; Rumble, Alexander; Thorn, Caroline (The University of Hull)
The introduction discusses the county boundary; the Hundreds, their rubrication, order, and revised name-forms; the state of the manuscript for the county; holdings recorded in other counties; related or 'satellite' texts; the "Inquisitio Comitatus Cantabrigiensis" (Cambridge Enquiry); the "Inquisitio Eliensis" (Ely Enquiry); and the editorial history of earlier versions of the notes, and the current state of the revision. Some material in this introduction derives from the original printed edition published by Phillimore (1981) and edited by Alexander Rumble.